'Some anti-malarials are too strong for your body, they will harm you.' Socio-cultural factors influencing pregnant women's adherence to anti-malarial treatment in rural Gambia. (December 2016) - Jaiteh, Fatou; Dierickx, Susan; Gryseels, Charlotte; O'Neill, Sarah; D'Alessandro, Umberto; Scott, Susana; Balen, Julie; Grietens, Koen
Abstract Background Despite declining prevalence of malaria in The Gambia, non-adherence to anti-malarial treatment still remains a challenge to control efforts. There is limited evidence on the socio-cultural factors that influence adherence to anti-malarial treatment in pregnancy. This study explored perceptions of malaria in pregnancy and their influence on adherence to anti-malarial treatment in a rural area of The Gambia. Methods An exploratory ethnographic study was conducted ancillary to a cluster-randomized trial on scheduled screening and treatment of malaria in pregnancy at village level in the Upper River Region of The Gambia from June to August 2014. Qualitative data were collected through interviewing and participant observation. Analysis was concurrent to data collection and carried out using NVivo 10. Results Although women had good bio-medical knowledge of malaria in pregnancy, adherence to anti-malarial treatment was generally perceived to be low. Pregnant women were perceived to discontinue the provided anti-malarial treatment after one or 2 days mainly due to non-recognition of symptoms, perceived ineffectiveness of the anti-malarial treatment, the perceived risks of medication and advice received from mothers-in-law. Conclusion Improving women's knowledge of malaria in pregnancy is not sufficient to assure adherence to anti-malarial treatment. Addressing structural barriers such as unclear health workers' messages about medication dosage, illness recognition, side effects of the medication and the integration of relatives, especially the mothers-in-law, in community-based programmes are additionally required.